From customer service to customer-driven services: Practitioner perspectives on a strategy for dealing with local authority austerity budgets. (November 2017) - Higson, Phil
This study aims to reflect on the views of public sector managers in relation to possible ways to cope with austerity budgeting and its impact on public services provided to local communities across a subregion. The investigation draws on empirical research based on a series of facilitated strategic workshops delivered to over 400 UK local authority middle managers. The findings indicate a suggested process model and framework to enable the implementation of a customer-driven approach to the delivery of local community public services. The intent of this study was to enable understanding of a particular case and to share that new understanding more widely. The overall approach is based on a 'common-sense' view of generalisability, in which readers will find value if the material resonates with their experience. This study is of potential benefit to researchers and those involved in developing effective and sustainable methods of coping with increasingly severe budgetary constraints on public sector local community provision. The study contributes to the extant literature by investigation of practitioner perspectives on these issues.